LIFE CYCLE ASSESSMENT AND COST BENEFIT ANALYSIS OF MUNICIPAL WASTE MANAGEMENT STRATEGIES - Soesanto, Qiyam Maulana Binu; Utomo, Laksamana Rayhan; Rachman, Indriyani; Matsumoto, Toru (Journal of Environmental Science and Sustainable Development, 2021)
Cimahi City is located in West Java Province, Indonesia. With a population of half million and the annual waste generation per capita reaching 0.48 kg/day, managing municipal waste has become increasingly challenging. To date, waste management costs in Cimahi City have not been specifically addressed. In addition to the total cost, there is also a plan to move the final landfill site from TPA Sarimukti, which is located approximately 34 km from the city center to a new final landfill site in TPA Legok Nangka, which is located approximately 56 km from Cimahi Municipality. This move will cause an increase in the cost to Cimahi Municipality. The aim of this study was to analyze the optimum waste management strategies for Cimahi City according to the environmental and cost-benefit impacts of the landfill site move. We used life cycle assessment and cost-benefit analysis to determine the optimum solution for waste management strategies of Cimahi City. Four scenarios, including the addition of waste banks, were compared as municipal waste management strategies. The switch of landfills did not contribute significantly to the total CO2 equivalent emitted. Increasing the number of waste banks could be an alternative to reducing the cost of disposing waste to landfills. Scenario (SC)-2 the scenario with additional government waste banks established, provided the highest net present value equal to IDR 1,428,622 per tonne of waste managed and was considered the most profitable in terms of the cost-benefit ratio. Hence, SC-2 was the most preferred for implementation in Cimahi City.